Lolodorfus, a new genus of net-winged beetles (Coleoptera: Lycidae: Dexorinae) from Cameroon - Bocakova, Milada (Zootaxa, 2014)
A new genus Lolodorfus is proposed within the subfamily Dexorinae and Lolodorfus flavus sp. nov. from Cameroon is described. Illustrations of diagnostic characters are given. The genus Mimolibnetis Pic, 1936 is transferred to the Dexorinae Bocak et Bocakova, 1989, and consequently the subfamily Mimolibnetinae Kazantsev, 2013 is considered to be a younger synonym of Dexorinae Bocak et Bocakova, 1989.
Keywords: brouci; mužské pohlaví; Cameroon; ženské pohlaví; zvířata; Female; Coleoptera; Kamerun; Male; Animals